Degree of satisfaction among users attended via telemedicine at the Primary Care Center II Lurín, Peru - Paz-Salinas, Brian Arturo (2023)
Objective: To identify the degree of satisfaction among users attended via telemedicine in the general medicine service at the Primary Care Center II Lurín (Peru) from October to December 2022. Methods: The research was observational, non-experimental, prospective, and descriptive. The sample consisted of 140 users selected through simple random sampling; the study was conducted with a 95% confdence level and a 5% sampling error. A questionnaire was administered to insured individuals who had been attended via teleconsultation, and descriptive statistics were applied to categorical variables. Results: A satisfaction score of 3.49 was found, corresponding to "neither dissatisfed nor satisfed"; in the tangible dimension, a satisfaction score of 2.52 was found, corresponding to "partially dissatisfed"; in the utilitydimension, a satisfaction score of 2.46 was found, corresponding to "partially dissatisfed"; and in the satisfaction dimension, a satisfaction score of 2.23 was found, corresponding to "partially dissatisfed." Regarding teleconsultation, a satisfaction score of 2.28 was found, corresponding to "partially dissatisfed." Conclusions: Users attended via telemedicine perceived themselves as partially dissatisfed with the care received.